THE EFFECT OF USING TEAM GAMES TOURNAMENT METHOD ON STUDENTS’ MASTERY IN IDENTIFYING PAST TENSE OF THE FIRST YEAR STUDENTS OF SMAN 1 PEKANBARU - Perangin-angin, G. Bernike Gustina; Delfi, Syofia; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed to find out whether or not there is a significant effect of Team Games Tournament (TGT) on the students’ mastery of the first year students of SMAN 1 Pekanbaru in identifying past tense. The research design is a pre-experimental research with one group pre-test and post-test design. The sample was X. MIA. 1 chosen by using cluster random sampling technique. In order to collect the data, the pre-test and post-test were administered and then the data were statistically analyzed by using the t-test formula. The result showed that the mean score of post-test was higher than mean score of pre-test (76.55 > 67.88). The value of t-test was 12.011 while the value of t-table in significance level 5% df = 35 was 2.030. Since the value of the t-test was higher than t-table, it can be concluded that Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It means that there was significant effect of Team Games Tournament (TGT) on the students’ mastery of the first year students of SMAN 1 Pekanbaru in identifying past tense. It is suggested that using Team Games Tournament (TGT) is one of the appropriate method to be implemented in teaching simple past tense so the students can be active and responsive in learning grammar.Key Words: Effect, TGT, Mastery, Past tense